Uji Coba Pembuatan dan Strategi Pemasaran Dodol Berbahan Dasar Labu Siam - Dewi andriani; Nila Sartika Achmadi; Andi Azizah Ramadhani (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2018)
ABSTRACT                 Chayote is a local vegetable with high nutrient which is sold with low price. Chayote can be produced into dodol with the following steps: sorting, peeling, cutting, washing, mashing, and then processing chayote into dodol. This research aims to find out how to measure people’s acceptance of chayote dodol and how to market it. This is an experimental research on how to make chayote dodol and descriptive research to describe the best marketing strategy to introduce chayote in the market. The population is students of Bosowa Polytechnic where 73 of them were chosen to become the sample to test the taste, color, scent, and texture of chayote dodol. There were three treatments: LS1 (100% chayote), LS2 (75% chayote), and L3 (50% chayote). Data was analyzed with descriptive statistic from Hedonic Test. The highest average score from the scent treatment was LS1 with 3.31 out of 5 score. From the taste, the respondents mostly chose LS1 with 2.88 average score. From the color, the respondents mostly chose LS2 with average score of 3.01. The last aspect was texture and mostly respondents chose LS1 with 3.00 average score. Based on the result, this research used 4Ps marketing strategy to introduce this product to the market.Keywords:  dodol, chayote, hedonic test, marketing strategy